ANALYSIS OF THIN CAPITALIZATION AND INVENTORY INTESITY AGGRESSIVITY TAXES ON FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Huda, Syamsul; Yuliati, Anik (Yayasan Pendidikan Belajar Berdikari, 2023)
The purpose of this research is to analyze influence Thin Capitalization and Inventory Intensity against aggressiveness tax. Study This including type study quantitative with use data secondary report finance. The population of this study was 30 companies in Indonesia Stock Exchange for period 2018-2022. The research sample used a purposive sampling method and obtained a sample of 13 companies. Data analysis using multiple regression analysis. The research results show that both Partial nor simultaneous Thin Capitalization and Inventory Intensity do not influence on aggressiveness tax during 2018-2022 period